Seasonal phytochemical study and antimicrobial potential of Vetiveria zizanioides roots - Dos Santos Delair Silveira; Oberger Júlia Vieira; Niero Rivaldo; Wagner Theodoro; Delle Monache Franco; Cruz Alexandre Bella; Martin-Quintal Zhelmy; Cechinel Filho Valdir (Acta Pharmaceutica)
This paper describes the seasonal phytochemical variation and the antimicrobial potential of V. zizanioides roots collected in Brazil. Considering the high levels of chemical constituents and their biological activity in dichloromethane fraction, the plants were grown in different seasons and the respective dichloromethane fractions were analyzed by gas chromatography-mass spectrometry. The antimicrobial activity was evaluated against several pathogenic microorganisms by determining the minimum inhibitory concentration (MIC) using the agar dilution method. Yields of dichloromethane fractions from plants collected in the autumn and spring occurred in a higher proportion than in other seasons. Khusimol (2) was isolated by column chromatography and identified by NMR and CG-MS, along with other sesquiterpenes, including β-vetivenene (1), vetiselinenol (3), isovalencenol (4), vetivenic acid (5), α-vetivone (6) and β-vetivone (7). Some extracts showed promising antimicrobial effects, with MICs ranging from 31.25 to 500 μg mL-1. Kushimol was slightly active against the tested microorganisms.